2010
DOI: 10.1002/asi.21350
|View full text |Cite
|
Sign up to set email alerts
|

Cuisine: Classification using stylistic feature sets and/or name‐based feature sets

Abstract: In contrast, the name-based feature sets are rather poor for these tasks. However, for the most complex task (ethnicity&time&place), a hill-climbing model using all feature sets succeeds in significantly improving the classification results. Most of the stylistic features (34 of 42) are language-independent and domain-independent. These features might be useful to the community at large, at least for rather simple tasks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…To overcome this combinatorial explosion for non-small values of n, several variants of hill-climbing have been proposed, (e.g., [68]). An application of TC to hill-climbing using feature sets was successfully demonstrated in HaCohen-Kerner et al [69].…”
Section: B Feature Sets and A Hill-climbing Modelmentioning
confidence: 99%
“…To overcome this combinatorial explosion for non-small values of n, several variants of hill-climbing have been proposed, (e.g., [68]). An application of TC to hill-climbing using feature sets was successfully demonstrated in HaCohen-Kerner et al [69].…”
Section: B Feature Sets and A Hill-climbing Modelmentioning
confidence: 99%
“…Other studies that are related to document classification and address the challenges of Hebrew involve the classification of Hebrew-Aramaic documents according to style (Koppel et al, 2006;Mughaz, 2003); authorship verification, including forgeries and pseudonyms (Koppel et al, 2003(Koppel et al, , 2004 and classification of texts according to their ethnic origin and their historical period (HaCohen-Kerner, Beck, Yehudai & Mughaz, 2006;HaCohen-Kerner, Mughaz et al, 2008;HaCohen-Kerner, Beck, Yehudai, Rosenstein & Mughaz, 2010).…”
Section: Related Workmentioning
confidence: 99%
“…The experimental analysis indicated that the presented scheme outperforms representation based on the distributional lexical measures, such as functions of vocabulary richness and frequencies of the occurrence of the most frequent words. HaCohen-Kerner et al [23] also utilised stylistic feature sets and name-based feature sets for text classification. Lee and Myaeng [10] presented a genre classification methodology based on document frequency ratios across genres and across subject classes.…”
Section: Literature Reviewmentioning
confidence: 99%